2013
DOI: 10.1021/jp4039573
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Pseudocapacitor Electrodes Based on α-Fe2O3/MnO2Core–Shell Nanowire Heterostructure Arrays

Abstract: A simple wet chemical technique has been employed to fabricate MnO2 nanolayer-coated α-Fe2O3/MnO2 core–shell nanowire heterostructure arrays to prepare unique pseudocapacitor electrodes. The coating of MnO2 on α-Fe2O3 nanowires is triggered by the reduction of KMnO4 solutions by the metallic (Au) film on which the polycrystalline α-Fe2O3 nanowires have been grown electrochemically. This metallic film also acts as the current collector by making direct contact with the arrays of the 1D nanoheterostructures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
126
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(128 citation statements)
references
References 54 publications
(100 reference statements)
2
126
0
Order By: Relevance
“…α-Fe 2 O 3 composites with different materials have been considered as potential candidates for pseudocapacitors, photocatalysis, high-performance anode material for lithium ion batteries, electromagnetic wave absorption materials etc. Sarkar et al [5] have reported that α-Fe 2 O 3 /MnO 2 nanoheterostructures exhibit excellent specific capacitance, high energy density, high power density, and long-term cyclic stability as compared with the bare α-Fe 2 O 3 nanowire electrodes. Their studies indicated that the α-Fe 2 O 3 /MnO 2 nanoheterostructure architecture is very promising for the next-generation * E-mail: pravanjan phy@yahoo.co.in high-performance pseudocapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…α-Fe 2 O 3 composites with different materials have been considered as potential candidates for pseudocapacitors, photocatalysis, high-performance anode material for lithium ion batteries, electromagnetic wave absorption materials etc. Sarkar et al [5] have reported that α-Fe 2 O 3 /MnO 2 nanoheterostructures exhibit excellent specific capacitance, high energy density, high power density, and long-term cyclic stability as compared with the bare α-Fe 2 O 3 nanowire electrodes. Their studies indicated that the α-Fe 2 O 3 /MnO 2 nanoheterostructure architecture is very promising for the next-generation * E-mail: pravanjan phy@yahoo.co.in high-performance pseudocapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, their energy densities still remain limited and there is a definite need to increase it to cope with the global energy demand for electric traction and nextgeneration portable electronic devices. 8 The energy density of supercapacitors can be enhanced by increasing their capacitance as well as their operating-potential window, which can be achieved more easily with asymmetric supercapacitors (ASCs) than with the symmetric supercapacitors (SSCs) since, with suitable combination of positive and negative electrode materials, the operational potential window as high as 2 V has been achieved even with aqueous electrolytes. 6,[9][10][11][12][13][14] In recent years, efforts have been expended to explore several ASCs with different electrode materials based on redox-active transition-metal oxides, like RuO 2 , 15 SnO 2 , 23 etc., which are not commercially viable owing to their high cost and environmental incompatibility.…”
mentioning
confidence: 99%
“…7,8 Hematite (α-Fe 2 O 3 ) is a promising negative electrode material for electrochemical capacitors (ECs) due to its high electrochem- * Electrochemical Society Member.…”
mentioning
confidence: 99%
“…6,7 In a core-shell nanostructure, nanometer-thin shell layer of electroactive materials significantly shortens ion-diffusion pathlength for effective ion-intercalation and deintercalation in conjunction with fast electron transfer to the core, while the highly conducting core, which serves as scaffold for electroactive shell, rapidly transfers the electrons to the current collector. 7,8 Hematite (α-Fe 2 O 3 ) is a promising negative electrode material for electrochemical capacitors (ECs) due to its high electrochem-ical activity, high theoretical-specific-capacitance, suitable negativepotential-window because of high hydrogen over-potential in aqueous electrolytes, mostly environment friendly and abundance in nature. [8][9][10][11] However, poor electrical conductivity (∼10 −14 S/cm) and short iondiffusion length limit its electrochemical performance significantly that can be overcome by creating oxygen vacancies within α-Fe 2 O 3 thin films.…”
mentioning
confidence: 99%
See 1 more Smart Citation